Effects of Mentorship Program on Academic Performance of Students in the Department of Medical Engineering at Kenya Medical Training College (KMTC), Nairobi Campus - Omondi, Agatha; Njiru, Lucy; Madete, June (International Journal of Health Sciences, 2024)
Purpose: This study investigates the effects of mentorship on the academic performance of students in the Department of Medical Engineering at Kenya Medical Training Centre, Nairobi Campus. Methodology: The study applied a descriptive cross-sectional survey that used quantitative methods of data collection. The primary data collection method was through interviews. The target population was drawn from Kenya Medical Training College (KMTC), Nairobi Campus as the unit of analysis while all the medical engineering students were the unit of observation. Stratified sampling was employed to categorize students by their year of study (years 1, 2 and 3), ensuring balanced representation across levels. From a total population of 530 students, 229 respondents were proportionally sampled from each subgroup using simple random sampling, with a random number generator assigning numbers to ensure unbiased selection. Data was collected using a questionnaire and analyzed through both descriptive and inferential analysis. Findings: Results revealed a β of 0.937 and a p-value of 0.001 between mentorship and the academic performance of students in the Department of Medical Engineering. This study reinforces the importance of mentorship in academic success, aligning with educational theories that emphasize student support systems as a critical factor in performance. The findings highlight the need for institutional frameworks to integrate mentorship programs more effectively into academic curricula, encouraging Kenya Medical Training Centre to formalize mentor training in communication, academic advising, and career development. Unique Contribution to Theory, Policy and Practice: The study highlights the value of group mentoring and peer-led initiatives, offering actionable insights to enhance mentoring effectiveness. Additionally, the study recommends allocating resources such as academic materials and counseling tools to mentors, promoting sustainable mentoring practices that maximize student outcomes. The contributions provide a foundation for future research on mentorship programs and support policies that foster academic excellence in technical training institutions.